2022
DOI: 10.1097/pcc.0000000000002906
|View full text |Cite
|
Sign up to set email alerts
|

Preload Dependence Fails to Predict Hemodynamic Instability During a Fluid Removal Challenge in Children*

Abstract: Fluid overload increases morbidity and mortality in PICU patients. Active fluid removal improves the prognosis but may worsen organ dysfunction. Preload dependence in adults does predict hemodynamic instability induced by a fluid removal challenge (FRC). We sought to investigate the diagnostic accuracy of dynamic and static markers of preload in predicting hemodynamic instability and reduction of stroke volume during an FRC in children. We followed the Standards for Reporting of Diagnostic Accuracy statement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We previously found that passive leg raising does not accurately predict cardiac index decrease nor hypotension following a fluid removal challenge of 500 mL UFnet over one hour in patients undergoing CRRT [ 10 ]. We observed the same results with calibrated abdominal compression to test preload responsiveness in children before a diuretics-induced fluid removal of 5 mL/kg over 2 h [ 11 ]. In our opinion, preload unresponsiveness better predicts the delay between the initiation of a UFnet at a higher rate rather than that of vascular refilling and the occurrence of hypovolemia.…”
Section: Commentmentioning
confidence: 75%
“…We previously found that passive leg raising does not accurately predict cardiac index decrease nor hypotension following a fluid removal challenge of 500 mL UFnet over one hour in patients undergoing CRRT [ 10 ]. We observed the same results with calibrated abdominal compression to test preload responsiveness in children before a diuretics-induced fluid removal of 5 mL/kg over 2 h [ 11 ]. In our opinion, preload unresponsiveness better predicts the delay between the initiation of a UFnet at a higher rate rather than that of vascular refilling and the occurrence of hypovolemia.…”
Section: Commentmentioning
confidence: 75%
“…The latest article from the Pediatric Cardiac Critical Care Consortium (PC4) registry describing potentially modifiable organizational and personnel factors on cardiac arrest prevention and rescue in the cardiac ICU (11). An article (12) and editorial (13) on fluid overload, intravascular volume, and fluid removal in the perioperative pediatric cardiac surgery population. A mixed-methods, single-center PC4-registry dataset of outcomes in 364 patients discharged to home directly from the cardiac ICU (14).…”
Section: “Pccm Connections” For Readersmentioning
confidence: 99%
“…In this issue of Pediatric Critical Care Medicine , Jacquet-Lagrèze et al (4) conducted a prospective observational study to assess the ability to predict hemodynamic instability with active fluid removal following pediatric cardiac surgery. The study included children 8 years old or younger ( n = 58) who were deemed to be fluid overloaded based on the presence of peripheral edema or a greater than 10% increase in body weight following surgery.…”
mentioning
confidence: 99%